Prevalence and contributing factors of malocclusion in Zhuang children aged 7–8 years in southern China - Mai, Wenjia; Xiao, Lijuan; Chen, Shaoyong; Chen, Shuang; Li, Andi; Zhang, Tingting; He, Haoyu; Zeng, Xiaojuan (Frontiers in Pediatrics, 2024)
Introduction: Malocclusion, a common oral health problem in children, is associated with several contributing factors. This study aimed to investigate the prevalence of mixed dentition stage malocclusion and its contributing factors in Chinese Zhuang children aged 7-8 years.Methods: Overall, 2,281 Zhuang children, about 7-8 years old, were randomly selected using a stratified whole-cluster sampling method from schools in counties in northwestern Guangxi, China. The children were examined on-site for malocclusion and caries by trained dentists, and basic data on the children were collected using questionnaires, including age, sex, parental education, parental accompaniment, and children's knowledge of malocclusion and treatment needs. Data were analyzed using the chi-square test and logistic regression analysis.The total prevalence of malocclusion in Zhuang children aged 7-8 years was 58.5%, with the highest prevalence of anterior crossbite tendency, and the prevalence of anterior crossbite and anterior edge-to-edge occlusion was 15.1% and 7.7%, respectively. This was followed by an anterior increased overjet of 13.3% and an inter-incisor spacing of 10.3%. The lowest prevalence was 2.7% for anterior open bite. Sex, parental accompaniment, parental education, and decayed, missing, and filled teeth of the first primary molar were factors that contributed to malocclusion in Zhuang children.Malocclusion is a common oral problem among Zhuang children. Therefore, more attention must be paid to the intervention and prevention of malocclusion. The impact factors should be controlled as early as possible.